Identity and synonymy of Dicroscelio Kieffer and description of Axea, a new genus from tropical Africa and Asia (Hymenoptera: Platygastroidea: Platygastridae) - Yoder, Matthew J.; Valerio, Alejandro A.; Masner, Lubomír; Johnson, Norman F. (Zootaxa, 2009)
Dicroscelio Kieffer is proposed as the senior synonym of Anteromorpha Dodd, Govinda Nixon, Aegyptoscelio Priesner, and Afroscelio Risbec, new synonymies. Members of the genus are found worldwide, but is most diverse in the Afrotropical and Oriental regions. The generic synonymies result in the following new combinations: D. abdominalis (Sundholm), new comb., D. africanus (Risbec), new comb., D. ancillus (Kozlov & Lê), new comb., D. cernatus (Kozlov & Lê), new comb., D. cuberatus (Kozlov & Lê), new comb., D. deccanensis (Sharma), new comb., D. depressus (Galloway), new comb., D. dubiosus (Perkins), new comb., D. ferrierei (Masner), new comb., D. frequens (Priesner), new comb., D. glaber (Sharma), new comb., D. incertus (Nixon), new comb., D. latus (Sundholm), new comb., D. malabaricus (Narendran), new comb., D. nonus (Nixon), new comb., D. obscurus (Sundholm), new comb., D. poussi (Risbec), new comb., D. reus (Nixon), new comb., D. rufipes (Ashmead), new comb., D. tuberculatus (Sharma), new comb., D. ueleensis (Risbec), new comb., D. undinus (Nixon), new comb. Lectotypes are designated for Anteromorpha australica Dodd and Afroscelio poussi Risbec. The name Dicroscelio was misapplied by Masner for an undescribed genus in the tribe Scelionini s.str.; Axea Masner & Johnson n.gen., is formally described, and 16 species are treated: A. adro Valerio & Yoder n.sp., A. atai Valerio & Yoder n.sp., A. atriceps (Kieffer) n.comb., A. dorothae Valerio & Yoder n.sp., A. eshu Valerio & Yoder n.sp., A. fisherhala Valerio & Yoder n.sp., A. kalanoro Valerio & Yoder n.sp., A. kilen Valerio & Yoder n.sp., A. mena Valerio & Yoder n.sp., A. nommo Valerio & Yoder n.sp., A. mwari Valerio & Yoder n.sp., A. talana Valerio & Yoder n.sp., A. yama Valerio & Yoder n.sp., A. yasigi Valerio & Yoder n.sp., A. yurugu Valerio & Yoder n.sp., and A. zanahary Valerio & Yoder n.sp.